A Validation Protocol for an Instrumented Wheel: A Comparison with a Dual-Roller Handrim Wheelchair Ergometer - Safiya Noury; Arnaud Hays; Nolwenn Poquerusse; Opale Vigié; Lorian Honnorat; Ilona Alberca; Mathieu Deves; Justin Regnaud; Arnaud Faupin (Methods and Protocols)
Measuring the propulsion performance of sport wheelchairs in ecological conditions remains complex due to variations inherent in real-world practice. This study aims to develop a validation protocol for an instrumented wheel designed to measure propulsion power under ecological conditions. The wheel’s precision was compared to that of the Lode Esseda roller ergometer, the gold standard for measuring the force exerted on both the left and right hands. Tests were conducted at three speeds (1, 2, and 3 m/s) on a multisport wheelchair. Results show a strong correlation between the two systems, confirmed by a repeated measures ANOVA test (p > 0.05) and a root mean square error (RMSE < 5%). Bland–Altman plots reveal good agreement despite discrepancies observed at high speeds, potentially due to mechanical limits. The proposed protocol validates the instrumented wheel and highlights the importance of multi-speed evaluation to ensure valid measurements in ecological conditions.